Costa Rica's implementation of the Framework Convention on Tobacco Control: Overcoming decades of industry dominance - Eric Crosbie; Patricia Sosa; Stanton A Glantz (Instituto Nacional de Salud Pública, 2016)
Objective. To analyze the passage of Costa Rica's 2012 tobacco control law. Materials and methods. Review of legislation, newspaper articles, and key informant interviews. Results. Tobacco control advocates, in close collaboration with international health groups, recruited national, regional and international experts to testify in the Legislative Assembly, implemented grassroots advocacy campaigns, and generated media coverage to enact strong legislation in March 2012 consistent with the World Health Organization Framework Convention on Tobacco Control, despite tobacco industry lobbying efforts that for decades blocked effective tobacco control legislation. Conclusion. Costa Rica's experience illustrates how with resources, good strategic planning, ag- gressive tactics and perseverance tobacco control advocates can overcome tobacco industry opposition in the Legislative Assembly and Executive Branch. This determined approach has positioned Costa Rica to become a regional leader in tobacco control.